E-Learning Methods Impact in Vocational Education - Firmansyah, Adimas; Samsudin, Ajeng Febriani; Aqmal, Reinaldo Yusuf; Sasmita, Asep Hadian; Dwiyanti, Vina (INVOTEC, 2021)
The development of science and technology, especially in the field of information and technology, has helped and supported progress in all fields, including education. Learning processes that utilize technology and information in providing vocational education or E-learning is an important part. E-learning provides flexible space and time benefits for educators and students. This research is a literature review to understand e-learning systems in learning, especially vocational learning, which has various challenges and aims to deal with specific and technical abilities in each specific vocational field. The literature search strategy uses the search for articles published in national and international scientific journals. The results of research on e-learning indicate that the e-learning method is beneficial for every student and is very effective because e-learning provides space, time and cost benefits for students and educators. In addition, various supporting tools in the assessment of affective, cognitive and psychomotor aspects are available. Even the soft skills needed by vocational education students can be facilitated through e-learning. Optimizing e-learning will have a good impact on vocational education in preparing graduates who are ready to work.